2006
DOI: 10.2337/dc06-1118
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Postprandial Glycemic Exposure

Abstract: OBJECTIVE -To determine the best predictors of total postprandial glycemic exposure and peak glucose concentrations in nondiabetic humans. RESEARCH DESIGN AND METHODS -Data from 203 nondiabetic volunteers who ingested a carbohydrate-containing mixed meal were analyzed.RESULTS -Fasting glucose and insulin concentrations were poor predictors of postprandial glucose area above basal (R 2 ϭ ϳ0.07, P Ͻ 0.001). The correlation was stronger for 2-h glucose concentration (R 2 ϭ 0.55, P Ͻ 0.001) and improved slightly b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Studies in children and adults (excluding pregnancy), for instance, have shown that individuals without diabetes spend 96% of their time between 70 and 140 mg/dL ( 6 ). They rarely reach glucose levels between 140 and 180 mg/dL, and if they do, it is only for a short time interval after meals ( 7 ). Therefore, some have proposed that time spent in the tight glucose range of 70–140 mg/dL (i.e., time in tight range [TITR]) may better reflect the CGM metric of euglycemia ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in children and adults (excluding pregnancy), for instance, have shown that individuals without diabetes spend 96% of their time between 70 and 140 mg/dL ( 6 ). They rarely reach glucose levels between 140 and 180 mg/dL, and if they do, it is only for a short time interval after meals ( 7 ). Therefore, some have proposed that time spent in the tight glucose range of 70–140 mg/dL (i.e., time in tight range [TITR]) may better reflect the CGM metric of euglycemia ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Postprandial (after a meal) glucose test are often performed to monitor the control of diabetes patients. However, according to Cohen et al [3], measures of 2-h glucose concentrations alone or combined with fasting concentration, body composition etc. are poor predictors of glycaemic exposure.…”
Section: Introductionmentioning
confidence: 99%